DUOPOLY MARKET COMPETITION OF PRICING AND SERVICE POLICIES UNDER A DUAL-SALE CHANNEL - Tsao, Yu-Chung; Linh, Vu Thuy; Chen, Tsung-Hui (International Journal of Industrial Engineering: Theory, Applications and Practice, 2022)
The Internet provides lower company operating costs, increased product sales, understanding of customer preferences, and closeness to customers. Direct channels break barriers between suppliers and customers and change customer consumption patterns. However, they can also lead to competition and conflicts between upstream and downstream members of the supply chain. This study contributes to supply chain management research by investigating the joint impact of pricing policy, service-level investment, and dual-channel supply chain competition in a duopoly manufacturer channel. By simulating conditions similar to the actual market, the numerical experiment conducted in this study yielded several insights into the management of the dual-channel architecture. A targeted rebate mechanism is used to eliminate channel conflicts and persuade injured parties to accept the introduction of an online channel.